Bringing dead proteins back to life - A Wustman, Brandon; Steele, John W; Sjoberg, Eric R; Stevens, Anthony C (eLife, 2014)
A small molecule called EMD 57033 can repair motor proteins that have stopped working as a result of stress.
Keywords: myosin; protein folding; allostery; pharmacological chaperone